AYYĀM AL-BĪḌ SYAR'I AND ASTRONOMY PERSPECTIVE (BETWEEN FASTING MOMENTUM AND SCIENTIFIC CALCULATION) - luayyin luayyin; M. Ihtirozun Ni'am (Fakultas Syari'ah dan Hukum UIN Walisongo, 2020)
Ayyām al-Bīdis a group of days in the hijri calendar system. Ayy termām al-Bīdobtained from the hadith of the Prophet which contains the command to fast for three days in each hijri month, which is sunnah. Ayy understandingām al-Bīdfrom the hadith of the Prophet is the date / day of the 13th, 14th, and 15th of the Hijri month. However, at a practical level, scholars differed when they mentioned the implementation of Ayy's fastām al-Bīd. There are 9 versions of this opinion. Here the writer wants to examine more deeply ayyām al-BīdThis is seen from a shar'i and astronomical perspective. The writer studies it with the research library method using the scientific-cum-doctriner approach. The data collected came from the books of hadith and fiqh, then analyzed with an astronomical approach. From this research, it was found that the meaning of the term Ayyām al-BīdIn the view of syar'i, it is the best time to observe the sunnah fast for three days every month. Matan hadith of the Prophet SAW regarding Ayyām al-Bīd which stipulates on the 13th, 14th and 15th of the Hijri month because that is the time when the full moon and lunar eclipses occur. From the review of astronomy Ayyām al-Bīdis the time when at night the Moon shines brighter than the other nights. Astronomically this can occur 4-5 days in the middle of the Hijri month.